Leaf Extracts of Moringa oleifera Cultivated in Baghdad: Characterization and Antimicrobial Potential against Endodontic Pathogens - Nada E. Shafiq; Anas F. Mahdee; Zainab Y. Mohammed Hasan (The Scientific World Journal)
The use of medicinal plant preparations to clean and disinfect root canal infection is gaining popularity. The aim of this study was to evaluate the bioactive composition of leaf extracts of Moringa oleifera plants cultivated in Iraq (specifically Baghdad) and their antimicrobial activity against selected root canal pathogens for potential application in endodontic treatment. Materials and Methods. Moringa leaf extracts were prepared either through cold maceration or warm digestion techniques to perform an ethanolic or aqueous extraction, respectively. Phytochemical detection was performed before thin layer chromatography (TLC) and high-performance liquid chromatography (HPLC) to measure flavonoids and phenolic compounds within both extracts. Then, their antimicrobial activities were investigated against Streptococcus mutans, Enterococcus faecalis, and Candida albicans through minimal inhibitory concentration (MIC), minimal bactericidal concentration (MBC), and agar well diffusion assay in comparison to NaOCl and Ca(OH)2. Results. Phytochemical screening showed several active ingredients but with higher expression of flavonoids and phenolic compounds. Also, different types of these compounds were detected through TLC and quantified by HPLC. MIC values for ethanolic extract against Streptococcus mutans, Enterococcus faecalis, and Candida albicans were 60, 65, and 55, respectively, while for aqueous extract, MIC values were 70, 80, and 50, respectively. Aqueous extract showed a higher inhibition zone than ethanolic extract for both Streptococcus mutans and Enterococcus faecalis with a statistically significant difference (p≤0.001) for all tested materials except with NaOCl and Ca(OH)2 in Streptococcus mutans and Enterococcus faecalis, respectively. The ethanolic extract showed a higher inhibition zone against Candida albicans, with a statistically significant difference (p≤0.001) for all tested materials. Conclusion. Ethanolic and aqueous extracts of Moringa oleifera leaves cultivated in Baghdad contain considerable quantities of phytochemicals, especially flavonoid and phenolic compounds, and demonstrated antimicrobial activities against selected endodontic pathogens. Therefore, Moringa leaf extracts could be suggested as an alternative antimicrobial material in endodontic treatment.